A critique of using age to ration health care. Issue 1 (March 1993) - Hunt, R W
Abstract : Daniel Callahan has argued that economic and social benefits would result from a policy of withholding medical treatments which prolong life in persons over a certain age. He claims 'the real goal of medicine' is to conquer death and prolong life with the use of technology, regardless of the age and quality of life of the patient, and this has been responsible for the escalation of health care expenditure. Callahan's proposal is based on economic rationalism but there is little evidence to suggest that substantial economic savings could be achieved. Moreover, his argument raises serious moral objections. A policy of withholding treatments from members of a social group involves elements of compulsion and discrimination, both of which would intrude on the doctor-patient relationship, undermine the autonomy of elderly patients, and invoke the slippery slope towards involuntary forms of euthanasia. Life-death decisions should be based on more than the one criterion of age, and take account of more relevant factors such as the patient's usual state of well-being, her/his expressed wishes, informed consent and the type of illness. Any move to the implementation and enforcement of the policy Callahan recommends would be rejected by health professionals and the public.